Networking banana and plantain: INIBAP annual report 1995 - International Network for the Improvement of Banana and Plantain (1996)
Summary French and Spanish This report contains 2 focus papers entitled ”Banana and plantain: the earliest fruit crops?” (discussing their origin and history of their domestication; written by E. de Langhe) and ”Musa nematologists' consortium: a step towards global collaboration” (discussing the objectives and activities, such as nematode culturing and screening for resistance/tolerance, of the consortium; written by D. de Waele). Reports on INIBAP activities around the world, and activities associated with Musa germplasm management and improvement are presented, together with details of information tools and services, visits, communications and publications, and staff publications and presentations. (Abstract © CAB ABSTRACTS, CAB International)